PENGARUH VARIASI WAKTU PENYIMPANAN TERHADAP STABILITAS REAGEN KERJA PADA HASIL PEMERIKSAAN KADAR KREATININ - Suryanata Kesuma; Suparno Putera Makkadafi; Silvi Marshela (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
Kidney is one of the organs of the body whose role is very important to maintain the stability of volume, osmolarity of extracellular fluid, and electrolyte composition. One of the parameters to determine kidney function that is usually done is creatinine examination. Preparation of working reagents is very important for accurate results in an examination. The purpose of this study was to determine the effect of storage on the stability of working reagents on creatinine examination. This type of research is a pseudo-experiment, to determine the difference between working reagents that are directly used with working reagents that are stored for several days. The research variables are the length of storage of work reagents, creatinine levels and storage temperature. The sample used in this study was normal creatinine control. The results were analyzed using Microsoft Excel and using the Kruskal Wallis Non Parametric test. The results of the study showed that the average reagent immediately and 5 days was 0.8 mg/dl and at 8 days 1.2 mg/dl, the accuracy obtained was -3.2% and 0.4%, the precision value obtained was 35.1% and 31.0%, in statistical tests significant results <0.05, meaning that there are differences in the results of examinations using working reagents that are used immediately and those stored for 5 and 8 days.